Integrate the adoption and readiness of digital technologies amongst accounting professionals towards the fourth industrial revolution - Sellywati Mohd Faizal; Nahariah Jaffar; Azleen Shabrina Mohd nor (Cogent Business & Management, 2022)
Due to the impact of Fourth Industrial Revolution (IR4.0), the accounting professionals are expected to undergo a big challenge. Currently, the development and integration of new technologies in society and industry have an unprecedented impact on the working environment. Therefore, there is a need for accounting professionals to diversify their ability to adopt IR4.0 and digital technologies. Upskilling and reskilling accountants to adopt digital technologies would help them to be relevant to future job demand. Whether the accounting professionals are now well-prepared to accept these digital technologies in their working lives has become a question. Therefore, this study develops a framework on the accounting professionals' willingness and readiness to adopt this change. This study aimed to assess the readiness of accountants to accept digital technologies by adopting and integrating the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Technology Readiness (TR). These theories proposed a framework to understand factors that influence accounting professionals to adopt digital technology in their workplace. The questionnaire was used and distributed randomly to accounting professionals from various organisations. The results found that performance expectancy, social influence and optimism support the prediction.
Keywords: 650; accounting professional; behavioural intention; digital technologies; TR; UTAUT